2016
DOI: 10.18051/univmed.2015.v34.3-9
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation improves heme biosynthesis in rats exposed to lead

Abstract: <p>BACKGROUND<br />Lead acetate (Pb) inhibits heme biosynthesis through inhibition of δ-aminolevulinic acid dehydrogenase (δ-ALAD), copro porphyrinogen<br />oxidase, and ferro chelatase. Zinc supplementation increases lead-binding<br />metallothionein proteins. The purpose of this study was to find evidence that zinc supplementation prior to lead exposure improves heme biosynthesis in rats</p><p>METHODS<br />This was a randomized post-test only control-group design stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…16 There ware association between Pb exposure and iron deficiency anemia in children 17 and there were association between Pb exposure in the air and blood Pb levels (p=0,000; r=0,606) and blood Pb levels and hemoglobin levels (p=0,000; r=-0,623). 18 The decrease of blood erythrocyte levels due to the lead induction is in accordance with previous research carried out by Santosa et al 19 Erythrocyte cell damage will cause destruction of erythrocyte cells and shorthening the age of erythrocyte, while increased levels of ROS will cause damage to the DNA and mitochondria resulting in apoptosis in the erythrocyte. 19 The ROS will inhibit the DNA repairing works initiated by p53 resulting in the stopping of cell cycle so that the aging will occurred in HSC or apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…16 There ware association between Pb exposure and iron deficiency anemia in children 17 and there were association between Pb exposure in the air and blood Pb levels (p=0,000; r=0,606) and blood Pb levels and hemoglobin levels (p=0,000; r=-0,623). 18 The decrease of blood erythrocyte levels due to the lead induction is in accordance with previous research carried out by Santosa et al 19 Erythrocyte cell damage will cause destruction of erythrocyte cells and shorthening the age of erythrocyte, while increased levels of ROS will cause damage to the DNA and mitochondria resulting in apoptosis in the erythrocyte. 19 The ROS will inhibit the DNA repairing works initiated by p53 resulting in the stopping of cell cycle so that the aging will occurred in HSC or apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…In a subsequent study, metallothioneins were proven to be able to prevent the inhibition of heme biosynthesis, hematopoiesis, and epithelial degeneration and necrosis of the renal tubule in rats exposed to lead. (14,15) This showed that metallothioneins are consistent metalbinding proteins in the tissues of all organisms. Regarding vegetable substances, it turns out that metallothioneins are abundantly present in the aqueous extract of IR Bagendit rice leaves.…”
Section: Introductionmentioning
confidence: 93%
“…(13) Metallothioneins can be synthesized in the liver as well as in the gastrointestinal wall through the absorption of various vegetable substances as well as micronutrients, such as zinc, and has been demonstrated to improve heme biosynthesis, hematopoiesis, epithelial degeneration and necrosis of the renal tubule, and basophilic stippling. (14,15) The study conducted by Santosa et al (16) reported that zinc supplementation administered in stepwise increasing daily doses to rats (Rattus norvegicus) was able to increase metallothioneins and that the effect had a positive correlation, i.e. the higher the administered zinc dose, the higher the mean metallothionein concentration.…”
Section: Introductionmentioning
confidence: 99%
“…This appears similar to the ring forms in malaria [62,63] Basophilic stippling Red blood cells present small RNA aggregates which are seen as little blue dots. In this case, fewer dots can be a characteristic of reticulocytes and more dots that of toxic bone marrow damage, thalassemia or myelodysplasia [64,65] Elliptocyte…”
Section: Babesiosismentioning
confidence: 99%